Isolation of Efficient Cellulose Decomposer in Sandy Cropland and Its Application in Straw Turnover in Agro-Pasture Ecotone of Northern China - Wang, Shaokun; Zhao, Xueyong; Suvdantsetseg, Balt; Lian, Jie (Frontiers in Environmental Science, 2020)
Slow organic material and nutrient turnover is one of the limiting processes in arid and semi-arid ecosystems, and cellulose decomposers play important role in straw turnover and nutrient return in cropland ecosystem in drylands. In order to moderate the limiting effect of material turnover, a high efficient cellulose decomposing fungus was screened from 85 cellulose decomposing fungi and we named the isolated fugus as NMCel-crop1 in the sandy cropland of Horqin Sandy Land in a semi-arid agro-pasture ecotone in northern China. This fungal decomposer was identified as Rhizomucor variabilis by using morphological and rDNA-ITS molecular methods. The optimized temperature for expressing its CMC (carboxymethyl cellulose) enzyme activity ranges from 40-55 °C. The CMC enzyme activity was significantly and highly produced by the NMCel-crop1 than that in situ soil in the cropland, and the filter paper decomposition rate was 82% in 7 days. The field straw decomposition experiment showed that the decomposition rate of maize straw infected by NMCel-crop1 reached at 92.5% in one year, which was 26% higher than that without infection. Straw turnover accelerated by NMCel-crop1 significantly increased soil organic carbon (SOC) and total nitrogen (TN) by 34.08% and 14.26%, respectively, indicating that the selected high efficient decomposing fungus could accelerate straw turnover rate, and increase soil organic carbon and nitrogen content and promote soil fertility and soil health in the sandy cropland, as well as potentially improve crop productivity and quality in the sustainable agriculture management of the arid and semi-arid sandy cropland.